The incipient national organized crime and its executioners, the improvised hitmen - Rodríguez Hurtado, Mario Pablo (2015)
A criminal modality that is becoming increasingly important nowadays and has many victims is the contract killing or the use of hitmen. The situation is aggravated by the presence of a process of crime institutionalization. The Peruvian government has responded to this problem typifying the aforementioned crime in the Criminal Code under condemns with are becoming longer. Was this the best solution?In the present article, the author answers this question by analyzing the penal types of contract killing while making a critic of the national criminal policy, taking into account the existence of other criminal types and other possible solutions, to finally prove its futility.